The individuals' discretionary behaviors at work. An overview and analysis of its growing interest - Fernandes, P. M. V.; Pereira, R.; Wiedenhöft, G.; Costa, P. (Heliyon, 2021)
Nearly forty years have passed since the term Organizational Citizenship Behavior appeared. Despite a current consensus among scholars about the citizenship gestures as prosocial acts of employees that benefit the organization, it does not apply commonly to the exponential growth of all OCB-related concepts. The concept's expansion has confused the researchers and practitioners, mainly when choosing the most appropriate instruments (constructs) and dimensions to use in their area of interest and context. A systematic literature review was conducted and 420 articles were analyzed. Results point that the trends on OCB-like behaviors goes higher, with an average annual growth rate of new studies of 3.13%. United States (39%) and China (25%) lead but some "under-studied" contexts like Africa, Latin America, the Caribbean, and Oceania start being studied towards OCB. New trends appear in the spectrum of the many different domains and disciplines related to OCB, while leadership and task performance remain the most studied domains and disciplines. In future studies, researchers must freely choose the OCB dimensions and constructs they want to use or adapt to meet their needs and research needs since there is no written rule about their use, only the care to be taken with the context and discipline studying.